Cuteness vs. usefulness: A dual perspective on service robot acceptance in the travel industry - Maeiro, J.; Dias, Á.; Pereira, L. (Journal of Theoretical and Applied Electronic Commerce Research, 2025)
The integration of service robots in the travel and hospitality industry is rapidly transforming customer interactions, offering both operational efficiencies and novel guest experiences. Despite their increasing presence, there remains a gap in understanding the factors influencing tourists’ acceptance of service robots, particularly the interplay between hedonic and functional motivations. Existing research has not fully explored how perceived cuteness and usefulness shape both initial interest and long-term acceptance of these technologies. This study addresses this gap by applying the Service Robot Acceptance Model (SRAM) and the Technology Acceptance Model (TAM) to examine the dual role of cuteness and usefulness in shaping consumer attitudes toward service robots in tourism. We employ a PLS-SEM approach based on survey data from 183 respondents, analyzing how these perceptions differ between individuals who have and have not previously interacted with service robots. Findings reveal that cuteness influences initial interest but does not translate into acceptance, whereas perceived usefulness and performance expectancy drive both interest and long-term acceptance. Additionally, we highlight the impact of sample composition on these results, recognizing potential biases and suggesting future research directions to improve generalizability. These insights offer practical guidance for tourism managers and marketers, helping them optimize service robot deployment by balancing aesthetic appeal with functional efficiency to enhance customer experiences.